Pendidikan Spiritualisme dalam Perspektif Al-Quran - Ruslan Ruslan; Andi Bunyamin; Andi Achruh (Al-Musannif, 2022)
This article aims to analyze spiritualism education in the Quran. The discussion focuses on four sub-discussions, namely: (1) The meaning of spiritualism in the Quran; (2) spiritual aspects of the Quran; (3) methods of Quran spirituality; and (4) the implications of Quran spirituality. This literature review documents various books, journals, and other research results as data sources. The collected data were then analyzed using content analysis techniques. The results of the study show that the concept of spiritualism in the perspective of the Koran is related to the world of the spirit, close to God, contains mysticism and interiority, and is equated with the essentials. Based on tracing the verses of the Quran, the three dimensions of spirituality in it are the dimension of transcendental, the dimension of norms, and the dimension of values. There are three methods of Quranic spirituality, namely tazakkur (remembrance of Allah), tafakkur (thinking about nature), and tadabbur (thinking about revelations or verses of Allah). The implications of the spirituality of the Koran are manifested in two terms in tasawuf spiritualism, namely al-maqāmat (the path to Sufism) and al-aḥwāl (the Sufi character).